2008
DOI: 10.1002/jsfa.3486
|View full text |Cite
|
Sign up to set email alerts
|

In vitro degradation by mixed rumen bacteria of 17 mono‐ and sesquiterpenes typical of winter and spring diets of goats on Basilitica rangelands (southern Italy)

Abstract: BACKGROUND: Nine monoterpenes (δ-3-carene, p-cymene, limonene, β-myrcene, (E)-and (Z)-β-ocimene, α-phellandrene, α-terpinene, γ -terpinene), seven oxygenated monoterpenes (1,8-cineole, linalool, (E)-and (Z)-linalool oxide, 4-terpinenol, α-terpineol, α-terpinolene) and one sesquiterpene (β-cedrene) were investigated for their degradability in the rumen microbial ecosystem. These molecules were identified as dominant terpenes in the winter and spring diets of milking goats in Basilicata (southern Italy).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
0
4

Year Published

2010
2010
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 49 publications
(51 reference statements)
1
9
0
4
Order By: Relevance
“…This supports our hypothesis that the terpene input concentrations in this study were high enough to support maximum terpene disappearance rates, which are therefore acceptable estimates of potential degradation of terpenes in the rumen. In addition, ranking the 14 terpenes by their relative amounts recovered was highly consistent with the results of a trial conducted under both experimentally and analytically dissimilar conditions (Malecky et al, 2009), in that terpenes were incubated with mixed rumen bacteria at a concentration 167-fold lower than in this study, and they were, then, extracted from fermentation broths using a head-space solid phase micro-extraction procedure. The relative amounts recovery ranged from 0.3% for a-phellandrene to 93% for (Z)-linalool oxide and correlated well with the data of this study (Y) according to the following regression equation: Y 5 X 3 0.962 (60.084) 1 6.9 (64.0; s.d.…”
Section: Discussionsupporting
confidence: 85%
“…This supports our hypothesis that the terpene input concentrations in this study were high enough to support maximum terpene disappearance rates, which are therefore acceptable estimates of potential degradation of terpenes in the rumen. In addition, ranking the 14 terpenes by their relative amounts recovered was highly consistent with the results of a trial conducted under both experimentally and analytically dissimilar conditions (Malecky et al, 2009), in that terpenes were incubated with mixed rumen bacteria at a concentration 167-fold lower than in this study, and they were, then, extracted from fermentation broths using a head-space solid phase micro-extraction procedure. The relative amounts recovery ranged from 0.3% for a-phellandrene to 93% for (Z)-linalool oxide and correlated well with the data of this study (Y) according to the following regression equation: Y 5 X 3 0.962 (60.084) 1 6.9 (64.0; s.d.…”
Section: Discussionsupporting
confidence: 85%
“…However, herbivores rarely suffer ill effects, since they have evolved a range of physiological mechanisms for detoxifying PSCs (Hoffman 1989; Duncan and Popi 2008; Fink‐Gremmels, 2010). Biotransformation of terpenes in ruminants may occur both at the rumen (Hylemon and Harder, 1999; Malecky et al., 2009b) and the lower intestine, as well as through phase I and II enzymes (Torregrossa and Dearing, 2009). Clearance or detoxification by hepatic (Egorin et al., 1996) or urinary routes (McLean et al., 1993) may occur when the concentration in the organism rises above a threshold.…”
Section: Introductionmentioning
confidence: 99%
“…The effect of degradation in the rumen on terpenes would vary according to the nature of terpene. Malecky et al (2009) after using in vitro incubation of seventeen terpenes with mixed rumen bacteria from dairy goats obtained recovery rates different markedly among terpenes, partly in relation to the presence of oxygen and rings in the molecules. Mathison et al (1999) indicated that alfalfa (Medicago sativa) saponins were rapidly released into rumen fluid and extensively degraded in the digestive tract of sheep but no attempt was made to determine how closely the products of degradation were related to the original molecules.…”
Section: Discussionmentioning
confidence: 99%